Tác động của quá trình quản trị tri thức tới kết quả hoạt động của các doanh nghiệp Việt Nam - Nguyễn Duy, Thành; Hoàng Văn, Nam; Đào Thị Thanh, Lam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Through knowledge-based view, this study assesses the impact of the knowledge process capability on firm performance of 482 Vietnamese enterprises. The results of SEM model analysis show that among the four factors of the knowledge process capability, knowledge acquisition, knowledge conversion and knowledge application have a positive impact on firm performance. However, knowledge protection insignificantly affects on firm performance. Among the factors of the knowledge process capability, knowledge conversion has the greatest impact on firm performance. In addition, knowledge acquisition also has a positive impact on knowledge application in Vietnamese enterprises. Beside, knowledge application is a partial intermediation in the relationship between knowledge acquisition and firm performance.
Keywords: Firm performance; Knowledge process capability; Knowledge-based view